Dampak Digitalisasi terhadap Praktik Manajemen Keberlanjutan di Sektor Bisnis - Iswandi Iswandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digitalization has become a key driver in the transformation of sustainability management practices across various business sectors. This study aims to explore the impact of digitalization on sustainability management, focusing on how digital technologies facilitate better decision-making, operational efficiency, and more sustainable resource management. The research method used was a systematic literature review, collecting data from various relevant journal sources, articles, and reports. The results show that the implementation of digital technologies, such as management information systems, artificial intelligence, and the Internet of Things (IoT), significantly improves corporate sustainability performance. The implications of this study emphasize the need to integrate digital technologies into sustainability management strategies to simultaneously achieve economic, social, and environmental goals.